دافعية الإنجاز الدراسي لدى طلبة المركز الوطني للمتميزين في سورية - شروف، أنساب (جامعة تشرين, 2017)
هدف البحث الحالي إلى تعرف مستوى دافعية الإنجاز الدراسي لدى طلبة المركز الوطني للمتميزين في سورية، بالإضافة إلى تحديد فيما إذا كان مستوى دافعية الإنجاز يختلف باختلاف المرحلة الدراسية أو الجنس أو الرغبة في الانتساب للمركز. لتحقيق أهداف البحث تم اعتماد المنهج الوصفي، حيث تم توزيع مقياس دافعية الإنجاز الدراسي على عينة مؤلفة من (170) طالبا وطالبة في المركز الوطني للمتميزين للعام الدراسي 2015-2016. بينت النتائج أن 74% من أفراد العينة يمتلكون مستوى متوسطا من دافعية الإنجاز و24% يمتلكون مستوى مرتفعا و1,76% يمتلكون مستوى منخفضا. كذلك، لم يختلف هذا المستوى باختلاف المرحلة الدراسية أو الجنس، لكنه اختلف باختلاف رغبة الطلبة بالانتساب للمركز، إذ أن الطلبة الذين انتسبوا للمركز بناء على رغبة شخصية منهم أو بناء على رغبة مشتركة بينهم وبين الأهل كانوا أكثر دافعية للإنجاز من الطلبة الذين انتسبوا للمركز بناء على رغبة الأهل دون رغبتهم الشخصية.
The aim of the current research is to determine the level of academic achievement motivation of the students in the national center for distinguished in Syria. In addition to determining whether the level of academic achievement motivation varies according to the stage of study or gender or the desire to join the Center. In order to achieve the objectives of the research, the descriptive approach was adopted. The motivation scale was distributed to a sample of 170 students at the National Center for distinguished in the academic year 2015-2016. The results showed that 74% of respondents had an average level of academic achievement motivation, 24% had a high level and 1.76% had a low level. Also, this level did not differ according to the stage of study or sex, but differed according to the students' desire to join the center. Students who joined the center with their personal desire or with a common desire between them and the parents were more motivated to achieve than students who joined the center with a desire of their parents without theirs.
Keywords: الإنجاز الدراسي -- الإرشاد النفسي -- السياسات التعليمية -- التعليم السوري